Modeling transverse impact on UHMWPE soft ballistic sub-laminate. (November 2017) - Haque, Bazle Z (Gama); Ali, Molla A; Gillespie, John W
High-performance ultra-high molecular weight polyethylene (UHMWPE) soft ballistic sub-laminates ([0/90] n, SBSL) are stacked to build a soft body armor pack (SBAP) that can defeat handgun projectiles. Transverse impact on single-layer [0/90] SBSL of different size is modeled with shell elements and is solved using LS-DYNA composite material model MAT54. The finite element (FE) model is validated using 1D and 2D theories for transverse impact. The validated FE models are then used to study the perforation behavior of a [0/90] SK76/PU SBSL under constant and variable velocity impact. Results show that the basal shape of the transverse deformation cone has a diamond shape; the cone wave speed along primary material direction agrees well with 2D membrane theory, there exists a minimum perforation velocity below which the SBSL will not perforate, the peak perforation force reduces with the size of the SBSL, and the work of perforation decreases with increasing speed. Detail perforation mechanics of [0/90] SK76/PU SBSL is presented for the first time.